Effectiveness of social-therapeutic treatment for serious offenders in juvenile detention: A quasi-experimental study of recidivism - Hausam, Joscha; Franke, Melissa; Lehmann, Robert J. B.; Dahle, Klaus-Peter (Frontiers in Psychiatry, 2022)
Due to legislative changes in Germany, there has been an increasing expansion of social-therapeutic facilities for juvenile offenders over the past 15 years. Social therapy comprises an eclectic mix of psychotherapeutic, educational, vocational, and recreational measures in a milieu-therapeutic setting to reduce recidivism of high-risk violent and sexual offenders. This study examined the effectiveness of social-therapeutic treatment on post-release recidivism among juvenile offenders. The sample included male offenders (n = 111) of the juvenile detention center in Berlin, Germany, aged 14–22 years, who were convicted of a violent (94%) or sexual offense (6%). Seventy-three subjects admitted to the social-therapeutic unit were compared to an offense-parallelized control group (n = 38) from the regular units using a propensity score based matching procedure. Initially, the groups did not differ with respect to risk (i.e., Level of Service Inventory - Revised) or risk-related characteristics (e.g., age). Subsequent Cox regression analyses revealed no average treatment effect on recidivism. Since the results indicated that the control group was not untreated, differential treatment effects were examined in a second step. School and vocational trainings had an effect on recidivism. The findings are discussed in light of the challenges in evaluating legally mandated offender treatment.